Tachycardia as a cardiovascular risk factor. Role of ambulatory heart rate - Paolo Palatini (Archives of Clinical Hypertension - Peertechz Publications, 2022)
There is a large body of evidence that resting Heart Rate (HR) is a strong predictor of cardiovascular events and mortality in hypertension [1,2]. This association was consistent across 9 Cohort studies and 7 large clinical trials performed on patients with hypertension [1].